2016
DOI: 10.1055/s-0036-1571317
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Early Screening for Gestational Diabetes on Perinatal Outcomes in High-Risk Women

Abstract: Objective To examine the benefits of early gestational diabetes mellitus (GDM) screening in a high risk population. Study Design Retrospective cohort of all singletons diagnosed with GDM with indications for early screening: GDM or macrosomia in a prior pregnancy or obesity. Subjects were classified as early (<20 weeks) or routine (>24 weeks) screening. Patients diagnosed with GDM were managed according to standard institutional protocols. Outcomes examined were cesarean delivery (CD), preeclampsia, large fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 14 publications
4
32
2
Order By: Relevance
“…In this study, gestational weight gain and glycemic control, but not the time of diagnosis, were independently associated with macrosomia in women with GDM [ 25 ]. The authors suggested that the higher frequency of insulin treatment, as consistently reported [ 17 , 18 , 21 , 24 – 26 , 45 ], and the lower gestational weight gain [ 21 , 24 , 25 ] in women with eGDM compared to women with late GDM might explain a similar prognosis in both groups in these studies. However, although insulin initiation was also earlier in eGDM than in late GDM, with a higher maximum daily insulin dose in the study by Sweeting et al, the prognosis was worse in women with eGDM [ 46 ].…”
Section: Resultssupporting
confidence: 61%
“…In this study, gestational weight gain and glycemic control, but not the time of diagnosis, were independently associated with macrosomia in women with GDM [ 25 ]. The authors suggested that the higher frequency of insulin treatment, as consistently reported [ 17 , 18 , 21 , 24 – 26 , 45 ], and the lower gestational weight gain [ 21 , 24 , 25 ] in women with eGDM compared to women with late GDM might explain a similar prognosis in both groups in these studies. However, although insulin initiation was also earlier in eGDM than in late GDM, with a higher maximum daily insulin dose in the study by Sweeting et al, the prognosis was worse in women with eGDM [ 46 ].…”
Section: Resultssupporting
confidence: 61%
“…However, when Hong et al investigated early GDM screening at < 20 weeks to routine screening at > 24 weeks, they did not detect a difference in cesarean delivery, preeclampsia, small for gestational age, or macrosomia. 12 This study demonstrating no benefit to early screening may lend support to our findings which suggest small lags in glycemic control created by delayed diagnosis with two-step screening might not have a clinically significant impact on perinatal outcomes. We acknowledge several study weaknesses.…”
Section: Discussionsupporting
confidence: 74%
“…Several studies have examined these adverse outcomes of high-risk women [12][13][14][15][16][17]. A recent Australian study concluded that despite early diagnosis, high-risk women suffered higher rates of preterm delivery, cesarean delivery, preeclampsia, and macrosomia, even a er excluding diabetes in pregnancy [12].…”
Section: Discussionmentioning
confidence: 99%
“…A recent Australian study concluded that despite early diagnosis, high-risk women suffered higher rates of preterm delivery, cesarean delivery, preeclampsia, and macrosomia, even a er excluding diabetes in pregnancy [12]. On the contrary, studies which used different diagnostic criteria have found that early diagnosed GDM was associated with a similar frequency of adverse outcomes, such as macrosomia, to routinely diagnosed GDM [3,14] and even women without GDM [18]. ese studies did not use current IADPSG criteria, limiting applicability to current practice.…”
Section: Discussionmentioning
confidence: 99%